2020
DOI: 10.1177/0972150920963069
|View full text |Cite
|
Sign up to set email alerts
|

Health Expenditure and Economic Growth Nexus: Empirical Evidence from South Asian Countries

Abstract: This study aims to empirically investigate the short-term and long-term effects of healthcare expenditure, institutional quality and domestic and foreign investments on the economic growth of South Asian countries during the period 1996–2018. The pooled ordinary least squares (OLS) and random effects models, Johansen–Fisher cointegration test and Granger causality test have been employed to assess the short-term and long-term relationships and the direction of causality among the variables. The cointegration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
4
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 59 publications
1
39
4
4
Order By: Relevance
“…All other relations were found not to have a causal link in between. Particularly with reference to institutions, the results of this study contradict Sethi et al (2020), which found unidirectional causality running from institutions to health expenditure. Source: Researchers' computation using E-views 9.0 *** denotes signi cant at 1% signi cant levels From Table 4 above, a signi cant negative relationship is noticed between health expenditure (LHE) and GDP per capita on the one hand, and also between Labour Force (LLF) and GDP in another hand in all the three models, namely panel OLS, Fully Modi ed OLS (FMOLS) and Dynamic panel OLS (DOLS) that a unit change in health expenditure or labour force will lead to a declining level of GDP per capita.…”
Section: Lhe ⇏ Lgdpcontrasting
confidence: 99%
See 1 more Smart Citation
“…All other relations were found not to have a causal link in between. Particularly with reference to institutions, the results of this study contradict Sethi et al (2020), which found unidirectional causality running from institutions to health expenditure. Source: Researchers' computation using E-views 9.0 *** denotes signi cant at 1% signi cant levels From Table 4 above, a signi cant negative relationship is noticed between health expenditure (LHE) and GDP per capita on the one hand, and also between Labour Force (LLF) and GDP in another hand in all the three models, namely panel OLS, Fully Modi ed OLS (FMOLS) and Dynamic panel OLS (DOLS) that a unit change in health expenditure or labour force will lead to a declining level of GDP per capita.…”
Section: Lhe ⇏ Lgdpcontrasting
confidence: 99%
“…Though the healthcare system is one of the chief indicators of a country's development (Radojicic et al 2020), the importance of health capital has only just caught the interest of researchers (Akingba et al 2018;Silva et al 2018). Despite its importance, the role of institutional quality in the relationship between economic growth and health expenditure is understudied (Sethi et al, 2020). Towards this, the study proceeds to study the role of health expenditure on the economic growth of the selected MENA countries.…”
Section: Introductionmentioning
confidence: 99%
“…While the impact of business cycles on health expenditure remains unclear and inconclusive. Some literature claims that health expenditure is pro-cyclical with business cycles ( 3 5 ). For example, Bedir ( 6 ), Payandeh et al ( 7 ), and Kumar et al ( 8 ) point out that the increase of residents' disposable income during boom periods guarantees their ability to pay for medical needs, resulting in more increases in health expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As we all know, health expenditure is affected not only by the above independent variables but also by many others, such as environmental quality and demographic characteristics. Referring to the existing studies ( 3 , 15 , 62 ), we control the following variables: environmental quality ( environment ), aging ratio ( aging ), urbanization level ( urban ), and gender ratio ( gender ).…”
Section: Models and Datamentioning
confidence: 99%
See 1 more Smart Citation